GENDER INEQUALITY BELOW THE „GLASS CEILING“ – CASE STUDY: THE HOTEL INDUSTRY IN VOJVODINA (SERBIA) - Garača, Vuk; Vukosav, Svetlana; Curaković, Danka; Bradić, Milan (Acta Geobalcanica (Skopje.Online), 2020)
Gender inequality is a common and modern subject in the hotel industry. The citations undoubtedly show the existence of glass ceilings in this area. The fact that women are discriminated concerning working position and the height of earning, irrespective of the level of education is proved by numerous domestic works and studies as well as the quantitative indicators of the Statistical Office of the Republic of Serbia. The goal of this paper is to confirm the gender inequality in the hotel industry of the northern Serbian province Vojvodina by using the qualitative indicators, stating attitudes, opinions and feelings. The structured interview was used as a basic method for gathering data. It was designed for women on the positions of medium and operative management, employed in ten representative hotels of Vojvodina. There is basic hypotheses about the existence of glass ceiling phenomena. The results of these interviews confirm previous quantitative indicators, as well as the basic hypothesis and most of the additional hypotheses.